2011
DOI: 10.4021/jocmr479w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin-To-Skin Contact on Preterm Infant Skin Barrier Function and Hospital-Acquired Infection

Abstract: BackgroundThe preterm infants' skin is structurally and functionally immature at birth because of immature stratum corneum barrier function, leading to problems with fluid loses, thermoregulation, and infection. Two parameters of barrier function can be non-invasively assessed: Stratum Corneum Hydration (SCH) and Transepidermal Water Loss (TEWL). Skin-to-Skin Care (SSC) is the proposed independent variable that might affect barrier function by decreasing TEWL and increasing SCH, thereby improving stratum corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In contrast, most previous studies have shown that infection rate decreases in infants who experience KMC [8,10,18]. Abouelfettoh et al [1] suggested that the fewer infections in preterm infants during KMC could be attributed to the improved skin barrier function and decreased transepidermal water loss.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, most previous studies have shown that infection rate decreases in infants who experience KMC [8,10,18]. Abouelfettoh et al [1] suggested that the fewer infections in preterm infants during KMC could be attributed to the improved skin barrier function and decreased transepidermal water loss.…”
Section: Discussionmentioning
confidence: 81%
“…28 None of the mothers had any signs or symptoms of infection during the first thirty days post discharge. 28 …”
Section: Data Synthesismentioning
confidence: 92%
“…No studies were found that examined the relationship between skin-to-skin contact and the infant microbiome, however one study did examine infection rates after mother skin-to-skin care in preterm infants. 28 After 5 consecutive days of skin-to-skin care for 90 minutes, only one infant developed a hospital-acquired infection within 7 days after the skin-to-skin care ended. 28 None of the mothers had any signs or symptoms of infection during the first thirty days post discharge.…”
Section: Data Synthesismentioning
confidence: 98%
See 2 more Smart Citations